Religious Reform: Parallels between the European Reformation and Contemporary Challenges in Muslim-Majority Societies - Almassry, Hazem (Contemporary Issues on Interfaith Law and Society, 2024)
This article explores into the profound dynamics of religious reform by drawing parallels between the European Reformation and the contemporary challenges facing Muslim-majority societies. While recognizing the unique contexts of these historical periods, the analysis sheds light on essential elements such as freedom, individualism, and the separation of religion from the state. It explores how these principles have played transformative roles in shaping Western modernity and their potential relevance in addressing current issues in Muslim-majority countries. The absence of a centralized religious authority in the latter context presents distinctive challenges, emphasizing the need for decentralized and context-specific reform strategies. The article underscores the importance of a multifaceted approach to reform, involving scholars, religious leaders, intellectuals, and civil society actors, in navigating the intricate path toward progress and renewal. Ultimately, this examination reaffirms the timeless pursuit of reform as a testament to human resilience and the enduring quest for positive change.